Data Localization Jungle : Debate over Cross-Border Data Flows and Their Regulation under the WTO - Martikainen, Kukka-Maaria (My University, 2022)
Data is both a valuable trade object itself and integral in enabling the supply of other services. Trading data, however, is not the same as trading other traditional goods, as there is much more to the game than just goods moving between jurisdictions. Data-related fears result in the need by the governments to assert more control over the movement of data. Data localization, defined as measures imposing geographical limitations on data that obstruct its free movement, is dreaded to be one of the most crucial barriers to the 21st century trade. As data localization increases, actors are turning to the WTO to help govern these issues. This study will look into data localization as a global phenomenon and how WTO law, particularly the GATS, eases the tensions caused by this phenomenon. This study will also provide ways to improve the WTO’s regulation on data-related issues. This study is based on a legal dogmatic approach but also utilizes research methods such as a sociology of law research method and a legal ethics research method. In the context of bringing forward ways to improve WTO law, this study also uses a de lege ferenda research method and a comparative law research method. The significant sources of information are the GATS agreement, important WTO cases and extensive bibliography written on the matter. Data localization is a complex concept practiced because of various different reasons. There is no general consensus on whether data localization is good or bad as it can be practiced for both legitimate and illegitimate reasons. It is clear, however, that if left unregulated, these measures have the capacity to hinder global trade and digital economy. WTO law is in desperate need of updating and, in order to regulate data-related issues more coherently, WTO must create a global governance model that is more data-specific, horizontal, and flexible.

Data on sekä arvokas kaupan kohde itsessään että olennainen osa muiden palvelujen tarjoamista. Datalla kaupankäyminen ei kuitenkaan ole sama asia kuin muilla perinteisillä tavaroilla kapankäyminen, koska pelissä on paljon muutakin kuin vain lainkäyttöalueiden välillä liikkuvia tavaroita. Dataa koskevat pelot johtavat siihen, että hallitukset haluavat entistä enenevissä määrin kontrolloida datan liikkuvuutta. Data lokalisaatio, joka voidaan määritellä maantieteellisiä rajoituksia datalle asettaviksi, sen vapaan liikkuvuuden estäviksi toimenpiteiksi, pelätään olevan yksi 2000-luvun kaupan kriittisimmistä esteistä. Lisääntynyt data lokalisaatio saa toimijat etsimään WTO:lta apua näiden asioiden sääntelemisessä. Tässä tutkimuksessa tarkastellaan data lokalisaatiota globaalina ilmiönä ja sitä, miten WTO:n laki, erityisesti GATS, lieventää ilmiön aiheuttamia jännitteitä. Tämä tutkimus myös tarjoaa tapoja, joiden avulla voidaan parantaa WTO:n sääntelyä dataan liittyvissä kysymyksissä. Tämä tutkimus perustuu oikeusdogmaattiseen lähestymistapaan, mutta siinä hyödynnetään myös muita tutkimusmenetelmiä, kuten oikeussosiologiaa ja oikeusetiikkaa. Tässä tutkimuksessa hyödynnetään myös de lege ferenda -tutkimusmenetelmää sekä oikeusvertailevaa tutkimusmenetelmää WTO:n lain parantamiseksi liittyvien tapojen esittelemisessä. Merkittäviä tietolähteitä ovat GATS-sopimus, merkittävät WTO:n oikeustapaukset ja aiheesta kirjoitettu laaja kirjallisuus. Data lokalisaatio on monimutkainen käsite, jota harjoitetaan useista eri syistä. Ei ole olemassa yleistä yksimielisyyttä siitä, onko data lokalisaatio hyvä vai huono asia, koska sitä voidaan harjoittaa sekä oikeutetuista että oikeudettomista syistä. On kuitenkin selvää, että jos data lokalisaatioon liittyvät toimenpiteet jätetään sääntelemättä, voivat ne vahingoittaa maailmanlaajuista kauppaa sekä digitaalista taloutta. WTO:n lainsäädäntö kaipaa kipeästi päivitystä, ja voidakseen säännellä dataan liittyviä asioita johdonmukaisemmin, WTO:n on luotava globaali hallintomalli, joka on data spesifimpi, horisontaalisempi ja joustavampi.
Keywords: data, data localization, cross-border data flows, international trade, international trade law, the WTO, the GATS